Bentuk Penyajian Rapai Bubee di Mee Pangwa Trienggadeng Pidie Jaya Provinsi Aceh - Intan Rizki Junita Tri Utami; Ediwar Ediwar (CV. Ulil Albab Corp, 2023)
This research is entirled “forms of serving Rapai Bubee in Gampong Mee Pangwa, Trienggadeng District, Pidie Jaya Regency”. Raising the issue of Rapai Bubee’s from of direction. The approach taken in this research uses a qualitative approach with descriptive research type. The data collection rechniques used were and decumentation. In terms of form, what is meant by from of presentation means that from is a fundamental element of a perfomance. These elements include artists, musical instruments, custumes and make-up, the songs presented, the perfomance venus and audience. In the presentation of Rapai Bubee, it is played by 18 people consisting of 14 musicians (Rapai musicians), 1 caliph, 2 sheikhs (the caliph and sheikh performance consists of four stages, namely Sapa, Sapa for the people of Aceh is the initial process of cummunication used to build trlationships, Saleum, Saleum is a term in Acehnese which means greeting. Bala Pari, Bala Pari is the third stage in the Rapai Bubee performance. Bala means disaster while Pari is the name for spirits or jin Lhee’s behavior. Lhee’s behavior is a rapai shot played with a slightly fast stroke tempo.